1982
DOI: 10.1073/pnas.79.19.6023
|View full text |Cite
|
Sign up to set email alerts
|

Mortality among health-conscious elderly Californians.

Abstract: In an attempt to obtain epidemiologic evidence regarding the mortality rate among vitamin supplement users, a prospective study was Only the cardiovascular SMR is significantly lower than 100%. The death rate for the males is approximately the same as that reported among other healthy nonsmoking questionnaire respondents, but the death rate for females is significantly less (P < 0.01). The only notable relationships between questions asked in 1974 and subsequent mortality are those indicating a higher mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 12 publications
0
31
0
Order By: Relevance
“…Depending on the population studied, rates of usage range from 26% to 80% (1,2). Most studies have reported that supplement use is more frequent among women, the welleducated, the typically healthy, and those who have higher incomes (3,4).…”
mentioning
confidence: 99%
“…Depending on the population studied, rates of usage range from 26% to 80% (1,2). Most studies have reported that supplement use is more frequent among women, the welleducated, the typically healthy, and those who have higher incomes (3,4).…”
mentioning
confidence: 99%
“…Physicians may partially contribute to this increased vitamin use since those caring for the elderly may frequently recommend a daily oral multivitamin, 5 despite literature suggesting the elderly may not need supplements 6–10 . Possible reasons multivitamins are given include the concern that the elderly often ingest inadequate amounts of vitamins, 11 and while intake does not always correlate with biochemical assessment of vitamin status, low vitamin levels have also been found in older people 11,12 .…”
mentioning
confidence: 99%
“…Physical activity in middle age at work andlor in leisure time has been associated with a lower incidence of CHD, independent of other risk factors recorded, in ten of thirteen cohort studies reviewed (47). Physical activity in the elderly, too, is a predictor of longer life expectancy among health-conscious elderly Californians: with increasing activity the proportion of deaths over six years fell from 46 O/ O to 10 O/ O (48).…”
Section: Physical Activitymentioning
confidence: 97%